Using finite element method based software to teach electrical machines-The linear switched reluctance actuator - Calado, M. Do Rosário (2019)
In this paper, the authors intend to propose a method to teach Electrical Machines in Electrical Engineering courses. The way that both in textbooks and classrooms treat this subject seems to limit students' understanding. The competences on electrical machines design and analysis are improved by a practical approach based on simulation and numerical analysis using Finite Element Method Software. As a complement to the previous teaching method, the students use an experimental test bench to verify the numerical results. A particular topic, concerning the study of the Linear Switched Reluctance Actuators, is here presented. Therefore, we propose a guideline for use in the classroom.